Joseph Conrad and Postcritique
XV, 233 p. 1 illus.
Keywords: ‘This collection of essays is a significant contribution to both Conrad studies and the critique / postcritique debate. Through a series of original, insightful and pertinently suggestive critical essays, focussed largely on canonical works by Conrad (Heart of Darkness, Lord Jim and The Secret Agent), it constitutes a paradigm shift in Conrad studies, while, at the same time, using Conrad as a case study, to demonstrate and explore a variety of postcritical approaches.’ —Professor Robert Hampson, FEA, FRSA, Research Fellow, The Institute of English Studies, University of London, UK This book takes a postcritical perspective on Joseph Conrad’s central texts, including Heart of Darkness, The Secret Agent, Under Western Eyes, and Lord Jim. Whereas critique is a form of reading that prioritizes suspicion, unmasking, and demystifying, postcritique ascribes positive value to the knowledge, affect, ethics, and politics that emerge from literature. The essays in this collection recognize the dark elements in Conrad’s fiction—deceit, vanity, avarice, lust, cynicism, and cruelty—yet they perceive hopefulness as well. Conrad’s skepticism unveils the dark heart of politics, and his critical heritage can feed our fear that humanity is incapable of improving. This Conrad is a well-known figure, but there is another, neglected Conrad that this book aims to bring to light, one who delves into the politics of hope as well as the politics of fear. Jay Parker is Assistant Professor in the English Department of the Hang SengUniversity of Hong Kong, Hong Kong. He has published articles on Conrad in relation to liberalism and to justice in Textual Practice, Law and Literature and The Conradian. He was awarded the Juliet McLauchlan Prize in 2012 and the Bruce Harkness Young Scholar Award in 2015 for his research on Conrad, and is fiction editor of the Hong Kong Review of Books, as well as Advisory Editor for The Conradian. He is currently completing a book on Conrad and Liberalism. Joyce Wexler is Professor Emerita of English at Loyola University Chicago, USA. She is the author of Violence without God: The Rhetorical Dilemma of Twentieth-Century Writers (2016), Who Paid for Modernism? Art, Money, and the Fiction of Conrad, Joyce, and Lawrence (1997), Laura Riding: A Bibliography (1981), and Laura Riding’s Pursuit ofTruth (1979). She currently serves as President of the Joseph Conrad Society of America. Chapters 1 and 2 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.